Business : - Ferrell, O. C. (McGraw-Hill/Irwin, 2008)
Business: A Changing World is the fastest growing introductory business textbook on the market, and for a simple reason. Unlike most brief textbooks on the market, which are trimmed and spliced from much longer works into an approximation of an essentials edition, Ferrell/Hirt/Ferrell is written from the ground up to be brief, lean, and flexible enough to enable you to cover just the topics you want at the level of depth you want, plus it doesn’t inherit out-dated examples from a hardback derivative. With market-leading teaching support and the most up to date content available, Business: A Changing World represents the best value available in the brief Introductory Business market. What sets Ferrell apart? An unrivaled mixture of topical depth, current content and the best teaching support around.